Circular Slits Map of Bounded Multiply Connected Regions - Ali W. K. Sangawi; Ali H. M. Murid; M. M. S. Nasser (Abstract and Applied Analysis)
We present a boundary integral equation method for the numerical conformal mapping of bounded multiply connected region onto a circular slit region. The method is based on some uniquely solvable boundary integral equations with adjoint classical, adjoint generalized, and modified Neumann kernels. These boundary integral equations are constructed from a boundary relationship satisfied by a function analytic on a multiply connected region. Some numerical examples are presented to illustrate the efficiency of the presented method.